SINERGI SECTOR KEUANGAN DAN RIIL DALAM MENDORONG PENCIPTAAN LAPANGAN KERJA DI INDONESIA PERIODE 1993-2023 - Putri, Sherina Fransiska; Susilowati, Dwi (Promosi: Jurnal Program Studi Pendidikan Ekonomi, 2025)
This study aims to analyze the dynamics of labor absorption in Indonesia during the period 1993-2023, focusing on the synergy of the financial sector and the real sector. This study uses a quantitative method with a descriptive and inferential approach. The data used are secondary data obtained from the Central Statistics Agency (BPS) and Bank Indonesia (BI). The data analysis techniques used are the Vector Error Correction Model (VECM), stationarity test, optimal lag determination, cointegration test, Granger causality, and VECM estimation. The results of the study indicate that the variables of the financial sector (inflation) and the real sector (number of MSMEs and wages) have a significant effect on labor absorption in Indonesia. Inflation has a negative effect, while the number of MSMEs and wages have a positive effect. The synergy between the financial sector and the real sector, as reflected in the growth of MSMEs and effective inflation control, plays an important role in creating sustainable employment. This study provides theoretical and practical contributions to the development of more effective economic policies in encouraging job creation in Indonesia.